Medical resource use and costs among rheumatoid arthritis patients receiving disease-modifying antirheumatic drug therapy. - Griffiths, R; Bar-Din, M; MacLean, C; Sullivan, E; Herbert, R; Yelin, E (2000)
OBJECTIVE: To identify costs among rheumatoid arthritis (RA) patients receiving alternative disease-modifying antirheumatic drug (DMARD) therapies. METHODS: Using managed care organization data, we identified members who (a) were prescribed any DMARD therapy for two consecutive months between July 1993 and February 1998, (b) were aged > or = 18 years, (c) had > or = 6 months of DMARD-free enrollment prior to the first DMARD, and (d) had a diagnosis of RA. RESULTS: The average age of the cohort (n = 571) was 51 years, and 70% were women. Mean duration of enrollment following initiation of DMARD therapy (observation period) was 19.5 months; 28.8% of patients switched DMARD regimens. The average monthly cost of care was $853, of which $294 (34%) was for RA-coded medical services. Monthly RA-coded costs varied by DMARD: hydroxychloroquine $227 (n = 252), methotrexate $340 (n = 185); sulfasalazine $233 (n = 49), and other mono/combination therapy $425 (n = 85) (P = 0.001). CONCLUSION: Costs of RA-coded care in patients receiving DMARDs are low and vary by DMARD.